Corruption as a collective action problem: Enabling the administrative control authority in Egypt - Gasser, Lameece (AUC Knowledge Fountain, 2018)
The fight against corruption has become a global priority in policy making circles, as corruption control grew to become a major industry backed by international alignment to curb corruption, especially in developing countries ridden with systemic corruption. Egypt, among other developing countries, is struggling in the fight against corruption, as a tool to promote investment and aid development progress. The Administrative Control Authority (ACA), the main anti-corruption body in Egypt, is the subject of this research. The research regards corruption as a collective action problem and utilizes the National Integrity System (NIS) – developed by Transparency International – as a conceptual framework to understand the extent to which the ACA is enabled to fulfill its mandate. Methodology includes semi-structured interviews with government officials in ACA and experts in international anti-corruption organizations. Qualitative data is analyzed based on three key dimensions, according to the Anti-Corruption Agencies pillar of the NIS; role of ACA in fighting corruption; governance mechanisms within the ACA that ensure its integrity and accountability; and the capacity of ACA to fulfill it role. Findings indicate to a shift in how the ACA understands its mandate, with more attention given to prevention measures besides investigation efforts. Main policy recommendations include; integrating corruption control reforms within wider good governance efforts; the need to demonstrate political will in the fight against corruption. Main operational recommendations include; integrate the ACA within a national accountability system, ensure the independence of the ACA through a transparent mechanism for appointing the President of the ACA, in addition to passing the needed legislations mainly the access to information law and protection of witnesses and whistleblowers law.